EFFECT OF FRUIT DECOCTION OF PHALERIA MACROCARPA ON URIC ACID LEVELS IN ELDERLY - Rostime Hermayerni Simanullang (Belitung Raya Foundation, 2018)
Background: The incidence of gout is rising both in the developed and developing countries not only in the elderly but also in young adults. Thus, the effort to reduce its incidence is necessary. Objective: To determine the effect of fruit decoction of phaleria macrocarpha on the levels of uric acid in the elderly. Methods: This was a pre-experimental study with pretest and posttetst design. This study was conducted at Sei Semayang Village North Sumatra from April to May 2017. There were 10 elderly selected using purposive sampling. Urid acid levels were measured using monitoring system of Easy Touch GCU. Independent t-test were used for data analysis. Results: Findings of this study showed that there was a significant difference in the mean value of the levels of uric acid before and after given fruit decoction of phaleria macrocarpa (p=0.004). Conclusion: There was a significant effect of fruit decoction of phaleria macrocarpa to decrease the level of uric acid in elderly. It is suggested that fruit decoctions of phaleria macrocarpa can be one of alternative therapies to prevent the increase of uric acid.